IUD insertion and reproductive planning performed by nurses in specialized primary care: An integrative review of the literature - Borges, Adriana Elisa dos Santos; Berto, Beatriz Trevizam; Peres, Giovana Suriani; Machado, Josilene Aparecida dos Santos; Souza, Tainá Monique de; Azzolin, Gabriela Marchiori Carmo (Seven Editora, 2024)
Objective: The following study aims to investigate the insertion of the IUD and the sexual rights of women from the reproductive planning carried out by nurses working in specialized primary care. Provide the synthesis of knowledge and results of its impacts through the research theme. Method: Integrative literature review in which we listed as a guiding question "What is the role of nursing in reproductive planning and the insertion of the IUD". For the bibliographic survey, the Virtual Health Library (VHL), Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Databases (BDENF), Scientific Electronic Library Online (SciELO) were used as databases. Results: Based on the scientific research and articles used, a critical thinking was built regarding the nurse’s performance. Many women are unaware of their sexual rights arranged in family planning and have fears about the functionality and insertion of the IUD. The propagation of information and health education by nurses is of paramount importance, so that in this way, we can provide qualified care, valuing the well-being of all involved and combating the paradigms imposed by society. Conclusion: Based on the other studies, it was possible to identify the importance of knowledge about reproductive and sexual planning in Brazilian society, since it is supported by Law No. 9,263 of January 12, 1996, which in addition to guaranteeing family planning, also clarifies the role of the state and the subjects involved in guaranteeing this right. Thus, increasing access to contraceptive methods offered by the public network and providing an improvement in the quality of life, also acting in the prevention and reduction of the maternal and neonatal mortality rate. DOI:https://doi.org/10.56238/sevened2024.001-016